Pendampingan Laporan Keuangan Dan Perhitungan Harga Pokok Penjualan (HPP) Pada Wisata Agro Melon Dan Badan Pengelola Usaha (BPU) Unila - Arie Sarjono Idris; Siti Khoirina; Rezeki Sembiring (BADAN PENERBIT STIEPARI PRESS, 2023)
Community Service (PKM) in collaboration with Wisata Agrro Melon and BPU Unila aims to provide guidance on financial reports and HPP calculations to activity participants. Activities carried out with the method of lectures, discussions and practices as well as evaluation. With this mentoring it is hoped that it can improve the performance of business actors. This PKM is expected to be useful for various parties involved in it.